Identifikasi Bakat Olahraga Renang Pada Tirto Karimun Swimming Club Tahun 2022 (Universitas Negeri Semarang, 2022)
Swimming is a sport that has a high existence at the world level. Anthropometry and Biomotor is one of the important elements and needed in swimming. The objectives to be achieved in this study are to determine: 1) there is a relationship between anthropometric measurements of crawl style skills, 2) there is a relationship between biomotor measurements and crawl style skills. The research applied in this research is correlational. The population in this study amounted to 30 people. The data analysis techniques used in this study were: 1) normality test of data with Kolmogrov-Smirnov test, 2) multicollinearity test, 3) heteroscedasticity test, 4) multiple linear regression test, 5) t-test. Based on the results of the analysis, it was found that the R Square value was 21% with the discussion showing that the value of sig t = 0.080 was greater than the value of = 5%. While the value of sig t = 0.044 is smaller than the value of = 5%. So it can be concluded that there is no significant correlation between anthropometric measurements and crawl style skills and conversely there is a significant correlation between biomotor measurements and crawl style skills.